ISLAMIC PERSPECTIVE IN INTERNATIONAL RELATIONS: AN ANALYSIS OF ITS DEVELOPMENT IN INDONESIA - Sofi Mubarok; Rudi Chandra (The Indonesian Islamic Studies and International Relations Association (Insiera), 2019)
This study is based on the rise of Islamic perspective in International Relations (IR) in several IR study programs in Indonesia. This study aims to elaborate the achievements of the development of Islamic perspectives in IR studies in Indonesia and what the factors influence the lack of productivity of scientific publications that related to Islamic International Relations. The subject of research are the head of the International Relations program under Islamic Universities (University of Darussalam Gontor, Muhammadiyah University of Yogyakarta, Islamic University of Indonesia, Sunan Ampel State Islamic University Surabaya and Muhammadiyah University of Malang) and members of Insiera (the Indonesian Islamic Studies and International Organization Relations Association) based in Yogyakarta. This study founded that the lack of quantity of Islamic International Relations-based scientific works in Indonesia is related to three conditions: first, the lack of development of the Islamic International Relations methodology in several universities; second, this temporary Islamic International Relations limited to specialization and not expertise; and the last, internal conditions on each campus, which is not related to the development of Islamic International Relations, has captured the attention of the majority of Islamic International Relations thinkers and researchers.Keywords: Islamic perspective; International